2008
DOI: 10.7589/0090-3558-44.4.1041
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Parasites Identified in the Feces of Eastern Spotted Skunks (Spilogale putorius) in Western Arkansas

Abstract: ABSTRACT:The endoparasite community of the eastern spotted skunk (Spilogale putorius) is poorly known. We surveyed parasites found in the feces of 29 eastern spotted skunks captured between March 2005 and January 2007 from a population in west-central Arkansas as part of a broader study of the ecology of the species. We identified 13 species (nine nematodes, four protozoa) from 82 fecal samples. Mean (6SD) number of species per individual skunk was 4.162.1, although this is likely an underestimate because some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…As expected, more intragenic variation of parasites was observed from this population of native wild skunks compared to the imported non-native population studied previously (Franssen et al., 2013). The higher prevalence of parasites in our study compared to a previous study of Spotted skunks (Lesmeister et al., 2008) is likely due to the difficulty in accurately identifying infected animals through fecal analysis compared to our method of visual inspection of the small intestine. Additionally, several of the animals in our study had very few worms infecting them.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…As expected, more intragenic variation of parasites was observed from this population of native wild skunks compared to the imported non-native population studied previously (Franssen et al., 2013). The higher prevalence of parasites in our study compared to a previous study of Spotted skunks (Lesmeister et al., 2008) is likely due to the difficulty in accurately identifying infected animals through fecal analysis compared to our method of visual inspection of the small intestine. Additionally, several of the animals in our study had very few worms infecting them.…”
Section: Discussioncontrasting
confidence: 80%
“…In contrast to the relative abundance of studies on B. procyonis , little is known of its closest relative, B. columnaris . Previous research using copromicroscopic detection has shown B. columnaris infection prevalence of ∼25% in a population of Eastern Spotted skunks ( Spilogale putorius ) (Lesmeister et al., 2008) and 25% prevalence in captive Striped skunks in Europe (d'Ovidio et al., 2017). To our knowledge, the prevalence of B. columnaris in wild populations of Striped skunks has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we identified possible pathways for transmission of nematode parasites such as Skrjabingylus spp. which require spotted skunks as definitive hosts to complete their life cycle (Kirkland Jr. and Kirkland 1983; Higdon and Gompper 2020; LaRose, Lesmeister, and Gompper 2021; Lesmeister et al 2008). Western spotted skunks have been shown to exhibit high prevalence and high severity of Skrjabingylus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The Shannon-Wiener index consolidates a measure of richness and evenness, and low evenness values (due to dominance by high-prevalence species) can diminish the ShannonWiener index values. Dominant representation of high-prevalence parasite species is common for parasite communities of coyotes (Samuel et al 1978, Lesmeister et al 2008, and heterogeneity in the distribution of parasites in wild animal populations is not unusual (O'Brien et al 2009). …”
Section: Parasite Evenness and Diversitymentioning
confidence: 99%
“…A double-centrifugation fecal flotation method was used to analyze coyote fecal samples (Zajac and Conboy 2006). This technique has been used for multiple surveys of coyote gastrointestinal parasitism in North America (Gau et al 1999, Gompper et al 2003, Lesmeister et al 2008). Sheather's sugar solution with specific gravity 1.26 was mixed with 4g of fecal samples to facilitate parasite eggs and oocysts to rise to the top of the solution.…”
Section: Laboratory Analysismentioning
confidence: 99%